"CALAMITAS TERRENA" OU "POENA DIVINA" : UNE APPROCHE ÉLIADIENNE DE LA PESTE DANS LE ROMAN "SORTEZ VOS MORTS" DE BRUNO LEYDET - Ciprian ONOFREI (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
Calamitas terrena or Poena divina: An Eliadian Approach to the Plague in the Novel Sortez vos morts by Bruno Leydet. The article proposes a dichotomous analysis of the outbreak of the Black Plague in Marseille (1720), described by French writer Bruno Leydet in the novel Sortez vos morts, which appeared in 2005. According to the grid established by Mircea Eliade, the analysis is built on two levels: the sacred and the profane. The religious as well as the modern perception of the disease and the use of a relevant lexis allow the bubonic plague to transgress the historical space, passing into the literary one. The plague epidemic in southern France is, in our view, not only a manifestation of the divine will to punish the sinful souls of the dead, but also the incarnation of greed and vicious side of the human being.